International Brotherhood of Teamsters records - International Brotherhood of Teamsters
Photocopies of correspondence, memoranda, reports, court orders, court and hearing decisions, transcripts of hearings, charts, graphs, lists, rosters, rules, computer lists, printed opinions, questionnaires, ballots, and recommendations documenting the union's 1991 convention and the election of national officers. Candidates for president of the union included Ronald Carey, R.V. Durham, and Walter J. Shea. Records were generated by the office of the election officer, Michael H. Holland, and describe the manner and method of voting, procedures for protest, plans for balloting, nomination of candidates, eligibility for office, conduct of participants, campaigning, and campaign contributions.
Photocopies produced from originals.
Labor organization formed in 1903 as International Brotherhood of Teamsters (IBT), the result of a merger between members of the Team Drivers' International Union (TDIU) and the Teamsters' National Union of America (TNU). Known from 1909 to 1992 as International Brotherhood of Teamsters, Chauffeurs, Stablemen and Helpers. Reverted to its pre-1909 name in October 1992.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carey, Ronald; Durham, R. V; Holland, Michael M; Shea, Walter J. -- 1929-; Labor unions -- Elections; Transport workers -- Labor unions